Estimation of ductility of a reinforced concrete member - Mahmood, Khalid; Ueda, Tamon; Wireland, Martin; Pichai Nimityongskul; Jain, Sudhir K.; Royal Government of Netherlands (Bangkok : Asian Institute of Technology, 1988)
In earthquake resistant design of structures, it is important to investigate the ductillty of reinforced concrete members under cyclic loading. A ductility index, which effectively represents the ductile behaviour of a reinforced concrete member, has been established. This ductility index is named as limiting ductility factor. A mathematical model, in the form of a damage model, has been established as a result of this study. The proposed model can be used to calculate the limiting ductility factor and corresponding number of cycles for a cantilever type reinforced concrete member subjected to any type of loading history with fully reversed loading cycles. The development of the model is based on theoretical, empirical and logical concepts. The proposed model gives results in appreciable agreement with the previously existing experimental data and confirms the conclusions drawn by previous researchers.
A Thesis Submitted in Partial Fulfilment of the Requirements for the Degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1989
Keywords: Reinforced concrete construction